Innate and acquired response of Neoseiulus barkeri and Neoseiulus californicus (Acari: Phytoseiidae) to spider mite induced plant volatiles - Ziba Hekmat; Azadeh Zahedi Golpayegani; Alireza Saboori; Sepideh Askarieh Yazdi (Persian Journal of Acarology)
Predators may adjust their foraging behavior according to herbivore induced plant volatiles innately or through learning. Here, first we investigated whether the phytoseiid predatory mites, Neoseiulus californicus and N. barkeri were innately able to respond to odors related to Tetranychus urticae infested bean leaves. The naïve predator females were reared on washed T. urticae as prey on filter paper with no experience of SIPV. The olfactory experiments showed that both N. barkeri and N. californicus significantly moved towards T. urticae infested bean leaves rather than clean air. Neoseiulus californicus significant preference of T. urticae infested bean leaves rather than clean tomato (as unfamiliar environment) confirmed the innate response in this species, while N. barkeri could not differentiate the latter odor sources so that its innate response considered weak. In a separate set of experiments, naïve N. californicus females with no preference towards SIPV were experienced by receiving odors related to T. urticae infested bean leaves. The changed response (significant preference) of the experienced individuals showed the predator ability for acquired response. As the predator paired the odor with food absence/presence, associated learning was suggested as the mechanism. No acquired response was recorded for N. barkeri.